The second ending : a novel - Hoffman, Michelle (Ballantine Books, 2023)
"A former prodigy refuses to believe her best years are behind her in this sparkling debut about second chances, unexpected joys, and the miraculous healing power of art and connection. It's a lot of pressure being compared to Mozart. Especially when you're only five. Prudence Childs was once the most famous kindergartner on the planet. She played at the White House, appeared on talk shows, and inspired a generation of children to take up piano. But as adolescence closed in, Prudence began to see that she was just another exploited child star, pushed to unnatural limits by her attention-hungry grandmother. Convinced that her "genius" was mostly a scam, Prudence ran away-both from performing and from her greedy handlers-as soon as she was old enough to vote. This one act of rebellion came with a cost-soon, Prudence was flat broke and utterly alone. Desperate for cash, she took a job writing commercial jingles, which earned her a fortune, but left her creatively adrift. Now forty-eight, after decades of questioning her talent, Prudence is determined to prove she's never lost her musical genius by competing on a wildly popular TV show. Her on-air rival is virtuoso pianist Alexei Petrov, a stunning young Internet sensation with a massive audience and a dreamy Russian accent. But Alexei's many charms are near the end of Prudence's long list of problems. The biggest threat to her comeback-aside from her own wavering confidence-is her terrible ex-husband, Bobby, who has evidence that she plagiarized her first and most iconic commercial jingle. If Prudence doesn't give Bobby the money he wants, he swears he'll use her new spotlight to take her down for good. But throughout the course of this novel brimming with quirky magic, humor, and emotional depth, Prudence might just defy the breathtaking odds and her overwhelming self-doubt-and find that her star still burns bright"--